A decline in the prevalence of angina pectoris: Data from the Nutrition and Health Survey in Taiwan. (1st April 2019) - Tsai, Ching-Ching; Hsieh, I-Chang; Jeng, Chii; Ho, Lun-Hui; Chu, Pao-Hsien; Chuang, Shao-Yuan
Abstract: Background: Angina pectoris (AP) is one of common symptoms of heart disease. The prevalence of AP varies by genders, age and ethnics. This study aimed to estimate the AP prevalence in adults and its change between surveys. Methods: Data was derived from the Nutrition and Health Survey in Taiwan (NAHSIT) between 1993 and 1996, and between 2005 and 2008. Participants aged ≥19 years old and grouped according to sex and age range (19–44.9, 45–64.9, and ≥65 years). The national weight prevalence rates in three types of AP (possible, definite, and confirmed) were estimated and we also estimated its change between surveys. Results: A total of 5031(1993–1996) and 4686 (2005–2008) adults were enrolled for this study. The aged-adjusted prevalence of possible, definite, and confirmed AP was 9.2%, 5.6%, and 2.1%, respectively, in 1993–1996, and 4.7%, 3.5%, and 1.1%, respectively, in 2005–2008. The age-adjusted prevalence of definite AP significantly declined from 5.6 (1993–1996) to 3.5 (2005–2008). Women had greater decline in the prevalence for possible (5.8% vs. 3.2%), definite (2.9% vs. 1.3%) and confirmed (1.6% vs. 0.5%) AP than men in both surveys. All AP prevalence rates increased by age in men in both surveys, however, the positive association between AP prevalence and age groups among women only was in 1993–1996. Conclusions: The AP prevalence significantly declined from 1993 to 1996 to 2005–2008. The AP prevalence in women was higher. The prevalence increased with age in men, but not in women. Continuous monitoring of AP prevalence is recommended to better understand the disease burden. Highlights: Angina pectoris is one of common clinical symptoms of coronary artery disease. Angina pectoris prevalence rates vary widely according to sex, age, and generations. Continuous pay attention to the prevalence of angina pectoris for better understanding the disease burden.